Storage Quality of Rista with Rosemary Extract as an Antioxidant - Hussain, S. A.; Salahuddin, Mir; Jalal, Heena; Wani, S. A.; Pal , M. A.; Bumla, Nazir (Journal of Meat Science, 2016)
The effect of incorporation of rosemary extract at 0.005% on the quality and storage stability of Rista was studied. All the physico-chemical parameters of raw emulsion, cooked product and gravy showed non-significant difference (p>0.05) between the treatments. Sensory scores of Rista showed non-significant (p>0.05) difference. Further, the cooked product was aerobically packaged in LDPE bags and stored at 4+1oC for a period of 3 weeks during which the product samples were drawn at weekly intervals and evaluated for pH, 2-thiobarbituric acid (TBA) value, microbiological quality and sensory attributes. The results indicated that the pH and TBA value of Rista samples increased significantly (p
Keywords: Meat emulsion; Natural antioxidant; Rancidity; Rista; Rosemary; Shelf-life